Eficiência de uso de nitrogênio e produtividade de milho em função da aplicação de biofertilizante com resíduo de pescado e Azospirillum brasilense - Oliveira, Alex Silva de (2016)
Use organic waste to biofertilizers production is a viable alternative that aims at sustainable production in agro-ecosystems. The aim was test the hypothesis that addition of waste of fish to replace the cattle manure in biofertilizers with added nitrogen fixing bacteria (Azospirillum brasilense) improve productivity and nitrogen use efficiency in organic maize cultivation. The treatments consisted of biofertilizers with fish waste (FW) proportions and cattle manure (CM): (B.0FW: 100CM) = 0% RP: 100% CM, (B.25FW: 75CM) = 25% FW: 33 75% CM, (B.50FW: 50CM) = 50% FW: 50% CM, (B.75FW: 25CM) = 75% FW: 25% CM and (B.100FW: 0CM) = 100% FW: 0% CM, with or without the addition of Azospirilum 35 brasilense in biofertilizer. The replacement of 100% of cattle manure for fish waste in 36 biofertilizers without bacteria increased by 27% maize yield. The addition of bacteria in 37 biofertilizers increases average productivity of treatment B.0FW: 100CM. The addition of thebacteria in biofertilizers increased remobilized nitrogen and post-anthesis absorbed compared to biofertilizers without bacteria. Independent of the addition or not the bacteria, treatment with 100% of cattle manure in biofertilizers achieved greater efficiency of nitrogen use compared to the other treatments. Our results indicate that replacement of manure by the fish waste for biofertilizer production is a good alternative to improve the production variables of the maize crop